Disruptive Marketing Communication for Customer Engagement. The New Frontiers of Mobile Instant Messaging. Issue 1 (2nd January 2019) - Marino, Vittoria; Lo Presti, Letizia
ABSTRACT: The aim of this paper is to evaluate the use of mobile instant messaging (MIM) apps from the perspective of the user. The objective is to verify what is the perceived usefulness, perceived value of use and usability of this new channel of communication utilized with customers and to verify if there are premises for considering instant messaging services as a new platform for customer engagement. Drawing from the Technology Acceptance Model, this study tests the consumers' perception of the use of mobile services with organizations. Data was made available for analysis from an online survey of 470 respondents. Results show that customers see MIM apps as an effective tool for customer care. Moreover, interaction through MIM apps adds value to the customer-brand relationship. MIM apps used as support to the relationship with customers can contribute to customer care, revealing it to be an excellent marketing tool in support of the customer journey. This research extends the understanding of customer engagement in the ambit of the instant messaging application used for business that so far has not been investigated. This work shows how instant messaging can optimize the benefits deriving from the adoption of disruptive innovations.